THE ROLE OF HUMOR IN IMPROVING THE EFFECTIVENESS OF GUS KAUTSAR'S DA'WAH ON THE YOUTUBE CHANNEL TERAS GUBUK - Mudzakir, Imam; Wijayanti, Rani Ika; Mutaqin, Zaenal (LP2M IAIN Syekh Nurjati Cirebon, 2025)
Although humor is important in adding a new dimension to the da'wah strategy, its role is merely supplementary. This study aims to determine the effectiveness of humor in Gus Kautsar's da'wah on the Teras Gubuk YouTube channel. This qualitative study uses a descriptive method with content analysis as the approach. The sample for this study was selected using purposive sampling. The researcher identified the Teras Gubuk YouTube channel and several informants as the subjects of the study. Data were collected through observation, interviews, and documentation. Data analysis techniques included reduction, presentation, and drawing conclusions. The results indicate that humor effectively conveys religious messages in Gus Kautsar's da'wah. .